Kardiyopulmoner Resüsitasyon - Uysal Kocabaş, Zehra (Yoğun Bakımda Tanı ve Tedavi, 2024)
Kardiyopulmoner resüsitasyon (KPR); kalbi duran bir kişide dolaşım ve solunumun tekrar çalıştırılması için uygulanan yöntemlerin bütünüdür. KPR 2’ye ayrılır: sıradan bireyler tarafından hastane dışı, ilaç ve ileri solunum tekniklerinin kullanılmadığı Temel Yaşam Desteği (TYD) ve sağlık personeli tarafından uygulanan İleri Yaşam Desteği (İYD). Şok, senkop, ileri kalp yetmezliği ve miyokardiyal iskemi bulguları olan hastalar stabil olmayan hastalar olup bu hastaların aritmilerinin ivedilikle tedavi edilmesi gerekir. Kardiyak arrest protokollerinin bilinmesi ve uygulanması resüsitasyon uğraşının en önemli unsurudur. Özellikle ileri kardiyak yaşam desteği uygulanan hastalarda hangi durumlarda ne zaman şok verileceği, hangi kardiyak arrest ritminde hangi tedavinin yapılması gerektiği çok önemlidir. Cardiopulmonary resuscitation (CPR) encompasses the techniques used to restore circulation and respiration in an individual whose heart has stopped. CPR is divided into two categories: Basic Life Support (BLS), which is administered by laypersons outside of a hospital setting without the use of drugs and advanced airway techniques, and Advanced Life Support (ALS), which is administered by healthcare professionals. Patients exhibiting signs of shock, syncope, advanced heart failure, and myocardial ischemia are considered unstable and require immediate treatment of their arrhythmias. Knowledge and implementation of cardiac arrest protocols are critical components of the resuscitation effort. Particularly in patients receiving advanced cardiac life support, it is crucial to know the appropriate situations and timing for defibrillation, as well as the specific treatments required for different cardiac arrest rhythms.